UJI EFEKTIVITAS ANTIBAKTERI EKSTRAK DAGING BUAH MAHKOTA DEWA (Phaleria macrocarpa) TERHADAP PERTUMBUHAN BAKTERI Escherichia coli - Wienaldi Wienaldi (Universitas Prima Indonesia, 2020)
The purpose of this research is to test the effectiveness of pure extract of the pulp of crown of god and extract of the pulp of crown of god with etanol as a drag in inhibiting the growth of the bacteria Escherichia coli. There are two samples be used, pure extract of the pulp of crown of god which has concentration 100% and extract of the pulp of crown of god with etanol as a drag has four concentration which is 1%, 5%, 10 % and 20%. The process of liquefaction is used according to the concentration could change the ability of the extract in inhibiting the growth of bacteria that could be tested by the disc diffusion method. The result also shows that all of the extract samples have the effectiveness of antibacterial on Escherichia coli. The average of inhibit zone which is formed by the pure extract of the pulp of crown of god is 9,3 mm and extract of the pulp of crown of god with etanol as a drag which has concentration 1% is 10,6 mm, 5% is 24,6 mm, 10 % is 15, 6 mm and 20% is 16,6 mm. these show that the big of concentration is used not straightly compare with the size of inhibit zone is formed.